Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1164/rccm.201207-1164oc
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Clinical Trial of Three Options for N95 Respirators and Medical Masks in Health Workers

Abstract: Continuous use of N95 respirators was more efficacious against CRI than intermittent use of N95 or medical masks. Most policies for HCWs recommend use of medical masks alone or targeted N95 respirator use. Continuous use of N95s resulted in significantly lower rates of bacterial colonization, a novel finding that points to more research on the clinical significance of bacterial infection in symptomatic HCWs. This study provides further data to inform occupational policy options for HCWs. Clinical trial registe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
232
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(256 citation statements)
references
References 40 publications
(58 reference statements)
4
232
1
4
Order By: Relevance
“…3 82 needs to be worn throughout the shift to be protective. 10 None of the four RCTs showed that medical masks were efficacious, although efficacy might have been at a lower level than the trials were able to detect. 9 10 Bacterial colonisation An analysis published in 2014 showed that laboratory confirmed bacterial colonisation (mainly Streptococcus pneumoniae and Haemophilus influenzae) is common in healthcare workers with symptoms of respiratory illness.…”
Section: Stat E O F T H E a Rt R Ev I E Wmentioning
confidence: 93%
See 2 more Smart Citations
“…3 82 needs to be worn throughout the shift to be protective. 10 None of the four RCTs showed that medical masks were efficacious, although efficacy might have been at a lower level than the trials were able to detect. 9 10 Bacterial colonisation An analysis published in 2014 showed that laboratory confirmed bacterial colonisation (mainly Streptococcus pneumoniae and Haemophilus influenzae) is common in healthcare workers with symptoms of respiratory illness.…”
Section: Stat E O F T H E a Rt R Ev I E Wmentioning
confidence: 93%
“…We identified only four RCTs of the clinical efficacy of facemasks or respirators in healthcare workers, which studied a diverse range of interventions and outcomes ( fig 1). [7][8][9][10] The updated 2014 WHO guidelines on personal protective equipment (PPE) cite two of these four trials, 44 but exclude the larger two. 9 10 The first trial, which was carried out in healthcare workers in Japan, randomised 32 workers to a medical mask group or a control arm.…”
Section: Stat E O F T H E a Rt R Ev I E Wmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no significant difference in confirmed viral infections (de-fined as a positive test from a symptomatic patient using a multiplex PCR to detect a group of respiratory pathogens including influenza) was found between the study arms. 17 This may reflect a true lack of difference between the 2 groups, or it may reflect an underpowering of the study to detect a difference. In the face of current uncertainties, CDC recommends the precautionary approach of using N95 respirators for influenza outbreaks that are greater in severity than seasonal strains to prevent severe cases of influenza among healthcare personnel.…”
Section: Discussionmentioning
confidence: 99%
“…Research shows that respirators provide better protection than masks for health workers, even when most of the pathogens identified are not spread by the airborne route (MacIntyre et al 2011;MacIntyre et al 2013), yet many bloggers positioned themselves as authoritative experts despite lacking any relevant expertise in the area. One blogger with a large following trivialized the need for respirators for health workers, even going as far as to say respirators were a "bad idea."…”
mentioning
confidence: 99%